The Illumination of Thunderclouds by Lightning: 4. Volumetric Thunderstorm Imagery. Issue 1 (10th January 2022) - Peterson, Michael; Mach, Douglas
Abstract: Optical instruments such as the Geostationary Lightning Mapper (GLM) detect lightning based on transient changes in cloud illumination. The horizontal location of lightning is determined from the coordinates of the pixels on the imaging array illuminated during the flash. However, the vertical position of the lightning pulses (approximated by GLM "groups") below the cloud top cannot be routinely measured from a single space‐based instrument. In our prior work, we have developed a machine learning algorithm that can infer optical source altitude for a given pulse based on how the optical energy is distributed across the group footprint and the local Advanced Baseline Imager Cloud‐Top Height (CTH). In this fourth part of our thundercloud illumination study, we leverage these source altitudes to generate volumetric GLM imagery of a Colombia thunderstorm. We find that 3D versions of the current GLM meteorological imagery products (that describe thunderstorm kinematics) and thundercloud imagery products (that depict how the flashes appear from space) provide additional insights into lightning activity in the thunderstorm that are lost in the vertical integration used to generate the current 2D GLM gridded products. This new volumetric imaging capability provides a more comprehensive picture of where lightning occurs in the storm, how its physical characteristics vary across three‐dimensional space, and how its optical emissions interact with surrounding the cloud medium. Plain Language Summary: Optical lightning imagers including NOAA's Geostationary Lightning Mapper (GLM) detect lightning by viewing the Earth from space with a specialized high‐speed camera that triggers whenever one of its pixels brightens in response to lightning illuminating the surrounding clouds. Lightning can be located and have its structure mapped in two‐dimensions by recording which pixels light up during the flash and projecting their angular coordinates down to the Earth. GLM data and imagery products are generated from this 2D composite view of the lightning activity in the thunderstorm. However, this is not a complete picture, as the frequency and behavior of lightning differs between vertical levels. We previously developed a method for retrieving source altitude based on how the energy from the optical pulses is spread horizontally across the cloud. In this study, we use these altitude estimates to construct 3D GLM imagery products that describe lightning across the full volume of the parent thunderstorm. This volumetric imagery provides additional insights into lightning and thunderstorms that are lost in the vertical integration employed by the current 2D GLM imagery products. Key Points: Source altitude information for each Geostationary Lightning Mapper group makes it possible to generate thunderstorm imagery as volumetric grids Example 3D imagery is generated for a Colombia thunderstorm—including Flash Extent Density, Min Flash Area, and optical energy grids These 3D grids provide additional information about storm structure that are masked by the vertical integration in the current 2D grids